The Berkeley DB Book - Yadava, Himanshu (Springer, 2017)
The Berkeley DB Book is a practical guide to the intricacies of the Berkeley DB. This book covers in-depth the complex design issues that are mostly only touched on in terse footnotes within the dense Berkeley DB reference manual. It explains the technology at a higher level and also covers the internals, providing generous code and design examples.